Capital Taxation, Long-run Growth, and Bequests - Lars Kunze (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
It has been shown that higher capital taxes can have a growth-enhancing effect when combined with a revenue-compensating cut in wage taxes (Uhlig and Yanagawa 1996; European Economic Review 40, 1521-1540) or with an expansion in productivity-increasing public services (Rivas 2003; European Economic Review 47, 477-503). The present paper demonstrates that these results critically hinge on the existence of a bequest motive. It is shown that a wage-tax cut is no longer growth-enhancing when bequests are operative. By way of contrast, increasing productive public services may well boost growth. The theoretical findings are illustrated by numerical simulations based on US data.
Keywords: D64; D91; H24; H50; O40; 330; Capital income taxation; public spending; overlapping generations; growth; family altruism; Kapitalertragsteuer; Lohnsteuer; Steuerreform; Steuerwirkung; Wirtschaftswachstum; Erbe; Privater Transfer; Overlapping Generations; Öffentliche Ausgaben; Theorie; USA